2012
DOI: 10.2478/v10298-012-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality and Crop Yields, After Utilization of Sewage Sludge on Agricultural Land, in the Moldavian Plain, Romania

Abstract: Soil Quality and Crop Yields, After Utilization of Sewage Sludge on Agricultural Land, in the Moldavian Plain, Romania Investigations conducted at the Podu-Iloaiei Agricultural Research Station, Iaşi County, have studied the influence of different sewage sludge rates on yield quality and quantity and soil agrochemical characteristics. Trials were set up in a five year-crop rotation, winter rape-wheat-maize-sunflower-wheat. Sewage sludge was applied every 2 years at rates of 20, 30, 40 and 60 t/ha, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Its landscape is wave‐like, with hilly areas, or shaped as low plateaus that are linked to a unitary geological surface, which is fragmented by the hydrological network. Furthermore, the landscape is covered with low plateaus or structural hills, with large, bridge‐like formations, at average altitudes of 160–180 m, and they are placed on sandy clays, covered with eluvial clays, which are representative for the entire geographical unit (Ailincăi, Jităreanu, Bucur, & Ailincăi, 2012; Ioniţă, Mărgineanu, & Hurjui, 2000; Romanescu & Constantin Stoleriu, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Its landscape is wave‐like, with hilly areas, or shaped as low plateaus that are linked to a unitary geological surface, which is fragmented by the hydrological network. Furthermore, the landscape is covered with low plateaus or structural hills, with large, bridge‐like formations, at average altitudes of 160–180 m, and they are placed on sandy clays, covered with eluvial clays, which are representative for the entire geographical unit (Ailincăi, Jităreanu, Bucur, & Ailincăi, 2012; Ioniţă, Mărgineanu, & Hurjui, 2000; Romanescu & Constantin Stoleriu, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Balanica et al, 2018 [ 19 ] showed that the content of heavy metals in sludge from five sewage treatment plants from South of Romania Giurgiu, Calarasi, Braila, Galati and Tulcea is below the maximum allowed limit. Ailincai et al, 2012 [ 20 ] showed that the two-year application of 30 t/ha of sludge from the sewage treatment plant in Iasi on an arable land in the Moldavian Plateau contributed to an improvement in soil properties through an increase in the organic carbon content from soil by 4.6 g/kg (28%), compared to the unfertilized variant. Utilization of sewage sludge in agriculture is of significant interest, due to nitrogen and phosphorus and microelements supply, Zn, Cu, B, and Mn.…”
Section: Discussionmentioning
confidence: 99%